AN ANALYSIS OF STUDENT’S RESILIENCE IN ONLINE ENGLISH CLASS DURING PANDEMIC ERA AT ENGLISH STUDY PROGRAM UNIVERSITAS MUHAMMADIYAH BENGKULU - Fadillah, Putri; Achmad Nurcholis, Ivan (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The COVID-19 pandemic has changed the way universities learn. Teaching and learning activities that usually take place face-to-face have evolved into virtual meetings in various online learning applications. This paper aims to analyze the resilience of students in handling online English courses from a perspective or from the perspective of coping with online learning challenges during the COVID-19 pandemic. This document collects 20 students who are actively participating in online learning activities as an example for the "Teaching English as a Foreign Language" course. Online learning offers a variety of teacher-led instruction. Instructions can be synchronous (communications where participants interact simultaneously, such as video conferencing, Zoom, Google Meet, and WebEx) or asynchronous (time-separated communications, such as email, Google Forms, streaming video content, posting handouts) and social media platforms). This study adopts a qualitative method. The researchers collected, read and highlighted each student's responses that were deemed relevant to the analysis. This article gives many answers to the challenges students face in online learning such as: skills, finding online learning media.